2017
DOI: 10.1116/1.4985002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cellular studies of molecular nanoparticle of iron (III)-tannic complexes; toward a low cost magnetic resonance imaging agent

Abstract: Herein, a new magnetic resonance imaging (MRI) agent based on molecular nanoparticles of iron(III)-tannic complexes (Fe-TA NPs) is reported. The paramagnetic and molecularlike Fe-TA NPs were successfully synthesized at room temperature within a few minutes without the use of any toxic agents or expensive equipment. The coordination states of the Fe-TA NPs were pH-dependent. The r relaxivity values of the bis-dominated and tris-dominated structures of the Fe-TA NPs were determined to be 6.31 and 5.24 mMs, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Under this condition, Fe–TA complexes undergo an iron-mediated self-assembly process to form nanosized Fe–TA complexes. It should be noted that PBS buffer (pH 7.4) was chosen as the reaction medium because this condition was suitable to form predominantly Tris-coordinated Fe–TA NPs (having a more stable structure) 28 , 35 .
Figure 1 ( a ) Schematic illustration of the preparation of Fe–TA NPs, ( b ) the TEM image of Fe–TA NPs, ( c ) typical characteristics of Fe–TA NPs.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Under this condition, Fe–TA complexes undergo an iron-mediated self-assembly process to form nanosized Fe–TA complexes. It should be noted that PBS buffer (pH 7.4) was chosen as the reaction medium because this condition was suitable to form predominantly Tris-coordinated Fe–TA NPs (having a more stable structure) 28 , 35 .
Figure 1 ( a ) Schematic illustration of the preparation of Fe–TA NPs, ( b ) the TEM image of Fe–TA NPs, ( c ) typical characteristics of Fe–TA NPs.
…”
Section: Resultsmentioning
confidence: 99%
“…This result is in consistent with the measured log P value of −1.0249, indicating good water solubility 41 . Previously, it has been demonstrated that molecular nanoparticles of Fe–TA complexes exhibit paramagnetism and enhance MRI signal intensity in T 1 -weighted imaging 28 . Similarly, the obtained Fe–TA NPs were also found to induce signal enhancement in T 1 -weighted images, with r 1 values of 3.08 mM −1 s −1 (in 4% acrylamide gel phantom), indicating that it can be used for increasing the sensitivity of MRI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, assembling structure of FTs can be changed or are degradable in the response to specific milieu. For example, an acidic environment is able to change the coordination state of FTs from Tris-dominant to be Bis-dominant structures [22]; reactive oxygen species like H2O2 are able to cleave Fe-O bonds of FTs. In addition, due to the existence of catechol group and metal-ligand bonding in FTs [23], covalent and coordinate interaction between FTs and biomolecules can occur in living subjects [15].…”
Section: Introductionmentioning
confidence: 99%